Development of a platform recommending 3D and spectral digitisation strategies - Stefanie Wefers; Ashish Karmacharya; Frank Boochs (Virtual Archaeology Review)
Spatial and spectral recording of cultural heritage objects is a complex task including data acquisition, processing and analysis involving different technical disciplines. Additionally, the development of a suitable digitisation strategy satisfying the expectations of the humanities experts needs an interdisciplinary dialogue often suffering from misunderstanding and knowledge gaps on both the technical and humanities sides. Through a concerted discussion experts from the cultural heritage and technical domains currently develop a so-called COSCHKR platform (Colour and Space in Cultural Heritage Knowledge Representation) which will give recommendations for spatial and spectral recording strategies adapted to the needs of the cultural heritage application. The platform will make use of an ontology through which the relevant parameters of the different domains involved in the recording, processing, analysis and dissemination of cultural heritage objects are hierarchically structured and are related through rule-based dependencies. Background and basis for this ontology is the fact that a deterministic relation exists between (1) the requirements of a cultural heritage application on spatial, spectral, as well as visual digital information of a cultural heritage object which itself has concrete physical characteristics and (2) the technical possibilities of the spectral and spatial recording devices. Through a case study which deals with the deformation analysis of wooden samples of cultural heritage artefacts this deterministic relationship is illustrated explaining the overall structure and development of the ontology. The aim of the COSCHKR platform is to support cultural heritage experts finding the best suitable recording strategy for their often unique physical cultural heritage object and research question. The platform will support them and will make them aware of the relevant parameters and limitations of the recording strategy with respect to the characteristics of the cultural heritage object, external influences, application, recording devices, and data.